Public spirometry for primary prevention of COPD - Zirlik, Sabine; Wich, Christina; Frieser, Markus; Hildner, Kai; Kleye, Christin; Neurath, Markus; Fuchs, Florian S. (Journal of Evaluation in Clinical Practice, 2014)
The most effective action for primary prevention of chronic obstructive lung disease is smoking cessation early enough. In secondary prevention, smokers with airway obstruction were more likely to quit smoking. The aim of this study was to evaluate the impact of a public spirometry on smoking habits in terms of primary prevention.Spirometry with its medical analysis was offered to visitors of a local public event called 'Lange Nacht der Wissenschaften' ('Long night of sciences'). The impact of results on smoking habits was evaluated in all smokers with an anonymized questionnaire afterwards.Two hundred fifty-seven people with the median age of 30 years (interquartile range 22-46) were examined. Out of 44 current smokers (17.1%), only two individuals showed a prebronchodilator FEV1/forced vital capacity-value <0.7. Fourteen smokers stated to have an increased motivation to quit smoking whereas 28 smokers declared that their motivation to quit smoking was independent of spirometry result. These smokers were significantly younger (median age 28 vs. 40 years, P = 0.025) without differences in spirometry results or smoking habits.In an unselected population with a high amount of younger adults, normal spirometry did not show a short-term benefit for primary prevention of chronic obstructive lung disease in terms of increasing motivation to quit smoking.
EVALuna2:1869